Spiritual and religious interventions as a complementary and supportive therapy in women with breast cancer: an integrative literature review - Sováriová Soósová, Mária; Suchanová, Renáta; Parová, Valéria; Hertelyová, Zdenka (Kontakt, 2024)
Introduction: Effective coping mechanisms and available support systems are essential to managing the disease and maintaining the mental health of women with breast cancer. It has been found that spirituality and religion can be an important supportive element in coping with cancer and its consequences. Aim: To analyse spiritual and religious (s/r) interventions provided by health care professionals to breast cancer patients, and their relationship to physical health, psychosocial, and spiritual outcomes. Methods: Integrative literature review of systematic literature reviews and/or meta-analysis was chosen. PubMed and Web of Science databases for the period 2013-2023 after entering the keywords "spiritual, religious, existential, positive psychology, mindfulness, interventions, breast cancer, cancer" in English were searched. Results: The review included 13 systematic reviews and/or meta-analyses (SRMA). Effect of mindfulness intervention was most frequently analysed. S/r interventions significantly associated with improvements in spiritual and existential well-being, quality of life and personal well-being, hope, optimism, cognitive functions and reductions of anxiety, depression, hopelessness, stress, and fatigue. Two SRMA found that s/r interventions were associated with improvements in cortisol levels, inflammatory cytokine activity, and lymphocyte function. Conclusion: The analysed studies showed that s/r interventions are associated with improved biological, psychosocial and spiritual outcomes, which supports the application of these interventions in clinical practice.
Keywords: Mindfulness; Humans; Complementary Therapies; spirituální terapie; Spiritual Therapies; Quality of Life; Psychotherapy; Review Literature as Topic; Female; Information Storage and Retrieval; lidé; kvalita života; náboženství a psychologie; Breast Neoplasms; ženské pohlaví; přehledová literatura jako téma; Religion and Psychology; psychoterapie; nádory prsu; Statistics as Topic; statistika jako téma; všímavost; ukládání a vyhledávání informací; komplementární terapie